IDEATIONAL MEANING OF A PROCEDURE TEXT “HOW TO DEVELOP TELEKINESIS” - Majid, Arfin (LANTERN (Journal on English Language, Culture and Literature), 2014)
Procedure text is a text that explains how to use instructions or shows how to make certain activities. In this case I took a procedure text which tells how to do telekinesis. The purpose of choosing the text is to show the ideational meaning of the text. In addition, since telekinesis is a concept that explains how to move a thing without touching it, therefore, I want to show the authors’ intention. In this final paper I used theory of systemic functional grammar, introduced by M. A. K. Halliday especially, which discussed the ideational meaning, as the basis of analyzing every clause in the text. Based on the analysis, I found two main ideas conveyed by the authors. The first is the belief. The second is capability.